“desarrollo de un marco referencial - Washington Antonio, Cevallos Gamboa. (2010)
Knowing that the Rule 14 issued by the National Constituent Assembly on July 22, 2008, establishes the obligation of the National Assessment and Accreditation (CONEA in Spanish) to develop a technical report on the level of the institutional performance of Higher Education Establishments to ensure their quality, promoting their depuration and improvement. Within the Evaluation Structure of the Ecuadorian University by the CONEA for the Students and Environment of Learning criteria, the emphasis is on new pedagogical models, the dimension of the learning environment or academic support including issues such as access to information, availability of information, computer labs and socalled ICT. The result from this study prepares a proposal for a viable framework model to solve the needs of Higher Education Institutions (IES in Spanish) or social groups that are incorporating the Information Technology and Communication in their Educational Models.